Implementasi Sistem Informasi Manajemen Keuangan di BUMDESMA Mentereng LKD Cikoneng Kabupaten Ciamis - Umar Ali Ahmad; Tora Fahrudin; Mera Kartika Delimayanti; Anggun Fitrian Isnawati; Wahyu Pamungkas; R. Rogers Dwiputra Setiady (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
BUMDESMA Mentereng LKD is a village financial institution in Cikoneng District, Ciamis Regency, which plays a vital role in supporting community economic empowerment. To date, financial management has relied on manual recording, leading to various challenges, such as validation delays, the risk of recording errors, and limited access to real-time information. These conditions hamper efficiency, transparency, and accountability in village financial governance. To address these challenges, a digital transformation was undertaken through the development and implementation of a website-based Financial Management Information System (SIMKUG). The system development process involved several stages, from needs analysis and prototype design to implementation, to user training and system outreach to managers. SIMKUG offers features capable of managing loan recording, installment payments, member and group management, cash transactions, financial reporting, and monitoring of non-performing loans in a more structured and integrated manner. The implementation of SIMKUG has been proven to increase operational efficiency, strengthen transparency, and improve village financial governance sustainably, providing significant benefits to managers and the community.